The World Is Gone Philosophy in Light of the Pandemic - Lambert, Gregg (University of Minnesota Press, 2022)
Exploring the existential implications of the Covid-19 crisis through meditationsPart personal memoir, part philosophical reflection and written in the midst of the pandemic in 2021, The World Is Gone employs the Robinson Crusoe fable to launch an existential investigation of the effects of extreme isolation, profound boredom, nightly insomnia, and the fear of madness associated with the loss of a world populated by others.Forerunners: Ideas First is a thought-in-process series of breakthrough digital publications. Written between fresh ideas and finished books, Forerunners draws on scholarly work initiated in notable blogs, social media, conference plenaries, journal articles, and the synergy of academic exchange. This is gray literature publishing: where intense thinking, change, and speculation take place in scholarship.